PERAN BADAN PENGEMBANG SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS APARATUR SIPIL NEGARA MELALUI JAKCORPU DI PEMERINTAHAN DK JAKARTA: Role Human Resources Development Agency In Improving Quality Of State Civil Apparatus Through Jakcorpu Special Regional Government Jakarta - Widya Nurjelita; Wijiningsih, Ninuk (Reformasi Hukum Trisakti, 2025)
The Human Resources Development Agency  plays a strategic role in improving the quality the State Civil Apparatus within the Jakarta Provincial Government In this research the problem formulation is. Is the implementation of the Jakcorpu program  BPSDM in accordance with Governor's Decree Number 1211 of 2021. This program designed provide structured competency-based training and development to answer the challenges of dynamic public service.  Implementation of BPSDM's functions in organizing Jakcorpu, effectiveness of the program in meeting ASN competency standards, and normative constraints related to policy implementation. The research method used is normative legal research, the nature of descriptive writing, the type of data using secondary data, and conclusions drawn using deductive logic. The result shows that Jakcorpu has become an innovative platform that integrates ASN development needs with regional policies, although challenges are still found, especially in aligning regulations and program financing. The conclusion discussion confirms that BPSDM through Jakcorpu plays an important role in forming professional and adaptive ASN. This program is not only relevant to increasing ASN capacity, but also a model HR development in other regional governments.